Attachment style moderates effects of FKBP5 polymorphisms and childhood abuse on post-traumatic stress symptoms: Results from the National Health and Resilience in Veterans Study. (21st April 2019) - Tamman, Amanda J. F.; Sippel, Lauren M.; Han, Shizhong; Neria, Yuval; Krystal, John H.; Southwick, Steven M.; Gelernter, Joel; Pietrzak, Robert H.
Abstract: Objectives: To determine the main and interactive effects of four FKBP5 polymorphisms (rs9296158, rs3800373, rs1360780 and rs9470080), childhood abuse and attachment style in predicting severity of PTSD symptoms in two independent, nationally representative samples of US military veterans. Methods: Data were analysed from two independent samples of European-American US military veterans who participated in the National Health and Resilience in Veterans Study ( N  = 1, 585 and 577 respectively). Results: Results revealed that carriage of two FKBP5 minor alleles, childhood abuse and insecure attachment style were associated with greater severity of PTSD symptoms. Gene × environment interactions were also observed, with the interaction of FKBP5 homozygous minor allele carriage and history of childhood abuse associated with greater severity of PTSD symptoms; however, these effects were fully counteracted by secure attachment style. Conclusions: Results of this study build on prior work demonstrating a gene × environment interaction between FKBP5 polymorphisms and childhood abuse in predicting risk for PTSD by suggesting that attachment style may moderate this effect. This study has implications for prevention and treatment efforts designed to promote a secure attachment style in veterans with high-risk FKBP5 genotypes and childhood abuse histories.